The Application of STAD- Cooperative Learning in Developing Integrated Science on Students Worksheet - Rahayu, Titik; Syafril, Syafrimen; Wati, Widya; Yuberti, Yuberti (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2017)
The application of Integrated teaching materials in teaching and learning science is very important, to support students acquire comprehensive knowledge and skills and make the learning process more memorable. Teachers must be good at choosing methods and packaging the teaching materials well to attract students' learning interests. This study aims to examine the analysis of the development of integrated Science on Student Worksheet using the steps of cooperative methods of Student Teams Achievement Divisions type. The study was conducted using a qualitative approach (Multi-case single-site case study design). The data were collected through analytical documents and analyzed thematically with NVIVO 10 software. The results showed that the steps to develop integrated science on Student Worksheet using cooperative method of Student Teams Achievement Divisions are: (1) In Student Worksheet there must be motivation and apperception; (2) team building; (3) presentations from teachers; (4) learning activities in teams must be heterogeneous; (5) implementation of individual quizzes; (6) awarding. The results of this study are discussed with various results of previous research.